The Effects of ESG Factors, Brand Purpose, and Brand Equity in Financial Product Purchase Intention among Different HNWI Age Groups in Thailand - Papasureeechote, Pooncharas; Wonglorsaichon, Phusit (Journal of Ecohumanism, 2025)
This study examines the effects of Environmental, Social, and Governance (ESG) factors, brand purpose, and brand equity on High-Net-Worth Individuals (HNWIs) purchase intentions for financial products, focusing on three age groups: 25–40, 41–60 and 61+ years old. Data were collected quantitatively from 876 Thai HNWIs by using a structured survey and asked those in the survey to do structured answering using regression analysis. It is found that predictors have different impact on aquaculture development, depending on age groups. Brand equity and brand purpose were key drivers for purchase intention for the 25–40 age group. Environmental responsibility, brand equity, and brand purpose had a great impact on the 41–60 age group. For the 61 and above age group, brand purpose was the only significant predictor of brand evaluation, and governance was marginally significant. These findings suggest that targeted marketing strategies are necessary to maximize these individual demographic segment’s priorities. The research shows the rising significance of ESG principles and brand factors in the formation of financial decisions of HNWIs and provides key insights for financial institutions to improve interaction with ethically conscious investors.